Zakat Sebagai Instrumen Ekonomi Islam Dalam Upaya Pemerataan Ekonomi Masyarakat - Mashudi; Binti Nur Asiyah; Johan Dwi Sutikno (AMAL: Jurnal Ekonomi Syariah, 2025)
This research is motivated by the large level of public expenditure gap that leads to inequality, with the Gini index as a reference. Considering Indonesia as a country with a large Muslim population, which is the second largest in the world. So, the contribution of zakat is considered an effort that can reduce the level of inequality. Therefore, this research was conducted with the aim of describing the contribution of zakat as an instrument of Islamic economics in the distribution of income in the context of economic equality. The research method is a qualitative approach with the type of literature research. The results of the research obtained that zakat is used as an instrument in Islamic economics, which has been proven to be effective as a means of income redistribution so that income is not distributed to certain groups but also flows to all levels of society, so that economic justice can occur. Furthermore, it can be seen that Indonesia has a great ability to manage zakat, if its management can contribute to the mustahik. The distribution of national ZIS in 2023 the poor occupy the top position in its allocation. Thus, the involvement of zakat can be used as a driver to improve both economic and social welfare, which is reflected in the achievement of justice in the economy or income distribution.